Novel LRRK2 mutations and other rare, non-BAP1-related candidate tumor predisposition gene variants in high-risk cancer families with mesothelioma and other tumors. Issue 18 (18th May 2021) - Cheung, Mitchell; Kadariya, Yuwaraj; Sementino, Eleonora; Hall, Michael J; Cozzi, Ilaria; Ascoli, Valeria; Ohar, Jill A; Testa, Joseph R
Abstract: There is irrefutable evidence that germline BRCA1-associated protein 1 gene ( BAP1 ) mutations contribute to malignant mesothelioma (MM) susceptibility. However, BAP1 mutations are not found in all cases with evidence of familial MM or in other high-risk cancer families affected by various cancers, including MM. The goal of this study was to use whole genome sequencing (WGS) to determine the frequency and types of germline gene variants occurring in 12 MM patients who were selected from a series of 141 asbestos-exposed MM patients with a family history of cancer but without a germline BAP1 mutation. WGS was also performed on two MM cases, a proband and sibling, from a previously reported family with multiple cases of MM without the inheritance of a predisposing BAP1 mutation. Altogether, germline DNA sequencing variants were identified in 21 cancer-related genes in 10 of the 13 probands. Germline indel, splice site and missense mutations and two large deletions were identified. Among the 13 MM index cases, 6 (46%) exhibited one or more predicted pathogenic mutations. Affected genes encode proteins involved in DNA repair ( ATM, ATR, BRCA2, BRIP1, CHEK2, MLH3, MUTYH, POLE, POLE4, POLQ and XRCC1 ), chromatin modification ( ARID1B, DNMT3A, JARID2 and SETD1B ) or other cellular pathways: leucine-rich repeat kinase 2 gene ( LRRK2 ) (two cases) and MSH4 . Notably, somatic truncating mutation or deletions of LRRK2 were occasionally found in MMs in The Cancer Genome Atlas, and the expression of LRRK2 was undetectable or downregulated in a majority of primary MMs and MM cell lines we examined, implying that loss of LRRK2 expression is a newly recognized tumor suppressor alteration in MM.